2008
DOI: 10.1152/ajpgi.00002.2008
|View full text |Cite
|
Sign up to set email alerts
|

Transient receptor potential vanilloid 4 mediates protease activated receptor 2-induced sensitization of colonic afferent nerves and visceral hyperalgesia

Abstract: Protease-activated receptor (PAR(2)) is expressed by nociceptive neurons and activated during inflammation by proteases from mast cells, the intestinal lumen, and the circulation. Agonists of PAR(2) cause hyperexcitability of intestinal sensory neurons and hyperalgesia to distensive stimuli by unknown mechanisms. We evaluated the role of the transient receptor potential vanilloid 4 (TRPV4) in PAR(2)-induced mechanical hyperalgesia of the mouse colon. Colonic sensory neurons, identified by retrograde tracing, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
137
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(142 citation statements)
references
References 59 publications
5
137
0
Order By: Relevance
“…In agreement, Cenac et al and Sipe et al furthermore showed that PAR2-induced hypersensitivity is mediated by the activation of TRPV4 (Cenac et al, 2008;Sipe et al, 2008). TRPV4 and PAR2 are co-expressed on the majority of spinal afferents innervating the murine colon and TRPV4 deletion or antagonism completely abolishes the sensitizing effects of PAR2 activation in these neurons (Sipe et al, 2008). However, because PAR2-induced Ca 2+ transients were not inhibited by TRPV4-targeted siRNA in DRG neurons, parallel, yet incremental, pathways for PAR2 and TRPV4 are suggested at the cellular level (Cenac et al, 2008).…”
Section: Trpv Channelssupporting
confidence: 69%
See 1 more Smart Citation
“…In agreement, Cenac et al and Sipe et al furthermore showed that PAR2-induced hypersensitivity is mediated by the activation of TRPV4 (Cenac et al, 2008;Sipe et al, 2008). TRPV4 and PAR2 are co-expressed on the majority of spinal afferents innervating the murine colon and TRPV4 deletion or antagonism completely abolishes the sensitizing effects of PAR2 activation in these neurons (Sipe et al, 2008). However, because PAR2-induced Ca 2+ transients were not inhibited by TRPV4-targeted siRNA in DRG neurons, parallel, yet incremental, pathways for PAR2 and TRPV4 are suggested at the cellular level (Cenac et al, 2008).…”
Section: Trpv Channelssupporting
confidence: 69%
“…In agreement, Cenac et al and Sipe et al furthermore showed that PAR2-induced hypersensitivity is mediated by the activation of TRPV4 (Cenac et al, 2008;Sipe et al, 2008). TRPV4 and PAR2 are co-expressed on the majority of spinal afferents innervating the murine colon and TRPV4 deletion or antagonism completely abolishes the sensitizing effects of PAR2 activation in these neurons (Sipe et al, 2008).…”
Section: Trpv Channelsmentioning
confidence: 55%
“…124 Activation of PAR2, by proteases released by mast cell degranulation, can lead to behavioural hypersensitivity and increased afferent firing via sensitization of TRPV4. 123,125 TRPA1 is the third TRP channel known to have a key role in setting the sensitivity of vascular afferents. It might also mediate PAR2-evoked sensitization in the gut 126 and/or bradykininmediated hypersensitivity.…”
Section: Trp Channels In Vascular Afferentsmentioning
confidence: 99%
“…Cat-S is also activated in inflammatory diseases including rheumatoid arthritis (4) and colitis (5). Given the established contributions of PAR 2 and TRPV4 to arthritis (63) and colitis (30,64,65), antagonists of Cat-S, PAR 2 , and TRPV4 may be valuable treatments for these and other inflammatory diseases.…”
mentioning
confidence: 99%